2015
DOI: 10.1111/jdv.13083
|View full text |Cite
|
Sign up to set email alerts
|

Mycosis fungoides: association of KIR ligands and HLADQB1*05 with bad prognosis of the disease

Abstract: Our observations suggest that the presence of the HLA-DQB1*05 alleles characterizes the patients with the poorest prognosis in MF. In addition, absence of the KIR-ligand epitope HLA-B Bw4 showed a trend of being more prominent in MF patients with the poorest prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
2
6
0
1
Order By: Relevance
“…[1] Study by Brazzelli et al indicated that the susceptibility of MF progression and prognosis depends on specific HLA alleles. [2,3] In vitro study showed that TOX promotes the proliferation of malignant cells in MF. [4] There were also other evidences showing different gene expression between early MF variants and that of late stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Study by Brazzelli et al indicated that the susceptibility of MF progression and prognosis depends on specific HLA alleles. [2,3] In vitro study showed that TOX promotes the proliferation of malignant cells in MF. [4] There were also other evidences showing different gene expression between early MF variants and that of late stage.…”
Section: Introductionmentioning
confidence: 99%
“…However, advanced stage of MF, especially with lymph nodes and visceral involvement, is associated with poor prognosis . Study by Brazzelli et al indicated that the susceptibility of MF progression and prognosis depends on specific HLA alleles . In vitro study showed that TOX promotes the proliferation of malignant cells in MF .…”
Section: Introductionmentioning
confidence: 99%
“…Our latest data shows that, 47 alleles of the DQB1 locus were identified and DQB1*05 was common with frequency (16.231%) in Chinese volunteers . One study suggested that the presence of the HLA‐DQB1*05 alleles characterizes the patients with the poorest prognosis in Mycosis fungoides …”
Section: Conflict Of Interestmentioning
confidence: 97%
“…Research Programme, IMIM-Hospital del Mar, Barcelona, Spain 14 Laboratori de Biologia Molecular, Servei de Patologia, Hospital del Mar, Barcelona, Spain 15 Departament de Genètica, Microbiologia i Estadística, Universitat de Barcelona, Barcelona, Spain 16 Institut de Recerca Sant Joan de Déu, Hospital Sant Joan de Déu, Barcelona, Spain 17 Institut de Biomedicina (IBUB), Universitat de Barcelona, Barcelona, Spain 18 Centro de Investigaciones Biomédicas en Red de Enfermedades Raras (CIBERER), Instituto de Salud Carlos III (ISCIII), Madrid, Spain…”
Section: Ack N Owled G M Entsunclassified